1998
DOI: 10.1007/s003830050496
|View full text |Cite
|
Sign up to set email alerts
|

Patent omphalomesenteric duct of the vermiform appendix in a neonate: congenital appendicoumbilical fistula

Abstract: Umbilical anomalies arise from fetal structures such as the omphalomesenteric duct (OMD) or urachus or from failure of closure of the umbilical fascial ring. Persistence of the OMD may lead to several anomalies including umbilical sinus, umbilical cyst, Meckel's diverticulum, or patent OMD (POMD). A POMD is usually associated with the ileum, but rarely may be with the caecum or appendix. We describe a POMD of the vermiform appendix and discuss the possible pathogenesis and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 6 publications
2
17
0
3
Order By: Relevance
“…[4][5][6] Similar to our experience, most of the subject are symptomatic in the neonatal period. Two of the subjects presenting in neonatal age succumbed to neonatal sepsis and dyselectrolytemia.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…[4][5][6] Similar to our experience, most of the subject are symptomatic in the neonatal period. Two of the subjects presenting in neonatal age succumbed to neonatal sepsis and dyselectrolytemia.…”
Section: Discussionsupporting
confidence: 59%
“…Although MD is common OMD anomaly in children, it is rare in infancy. [5,6] In our study too only in one case MD was found.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The most frequently seen of the aforementioned spectrum of findings is the Meckel's diverticulum and it is reported to be present in only 2-3% of people [5], and to be more symptomatic in males. The appendico-umbilical fistula is believed to be a variant of the patent omphalomesenteric duct, one that connected with the appendix instead of the distal ileum or other places like the cecum or the ascending colon [2], and that indeed is the diagnosis in this case.…”
Section: Discussionmentioning
confidence: 75%
“…These anomalies are in a spectrum and present in various forms, ranging from the infamous Meckel's diverticulum to a fibrous nonpatent connection between the umbilicus and the distal ileum, to a patent connection between the umbilicus and the intestine, the patent omphalomesenteric duct. It is normally observed as a connection with the distal ileum but has been known to connect with the cecum, ascending colon and the appendix [2,3]. We present the case of a two-month-old female child who was referred to us with complaints of failure of healing of the umbilical stump and the discharge of intestinal contents via the umbilicus.…”
Section: Introductionmentioning
confidence: 99%